An investigation into students' study habit in volumetric analysis in the senior secondary provision: A case study in Ondo State, Nigeria - Tunde, O.; Oke, O.K.; Alam, G.M. (Academic Journals, 2010)
An investigation was carried out on students' study habit in volumetric analysis at the senior secondary school level in Ondo State. A descriptive research design was adopted in the study. Questionnaire on study habit inventory was adapted and used to collect information from the respondents at various sampled schools. The sample comprised 240 senior secondary II chemistry students drawn from six schools in Akure South Local Government Area of Ondo State. The hypotheses investigated with respect to students' study habit problems such as home work/ assignment, reading and note-taking, students' concentration, time allocation, teachers' consultation as human variables were analyzed using chi-square statistics at 0.05 level of significance. The results indicated that the main sources of students' study problems have strong influence on students' study habit which is causally related to the performance and consequently the efficiency of the students during the practical lesson in volumetric analysis. Based on the findings of this study, it was recommended that chemistry teachers need proper exposure and orientation to some psychological study problems in order to understand students' developmental and intellectual progress so as to improved learners' performances. Hence, there is a need for workshops and seminar for teachers where the importance of effective study habit behavioural pattern would be stressed.